A Sociological Review of China's Social Credit Systems and Guanxi Opportunities for Social Mobility. Issue 5 (26th February 2020) - Raghunath, Nilanjan
Abstract: This paper proposes a novel understanding of social mobility in China by exploring the literature on social credit systems. I propose that social credit systems, which include credit rating systems and factors of social governance, can affect occupational attainment, as they may influence or function in tandem with guanxi networks. Through social credit systems, there could possibly be a new order of stratification powered by norms of social conformity. These systems can curtail social mobility efforts by designating some individuals as high risk. In addition, these systems can regulate social behaviors, as actions that are considered "right" are rewarded, while "wrong" actions result in penalties.